Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1667/rr2372.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gap Junction Communication and Oxidative Stress in the Propagation of Toxic Effects among High-Dose α-Particle-Irradiated Human Cells

Abstract: We investigated the roles of gap junction communication and oxidative stress in modulating potentially lethal damage repair in human fibroblast cultures exposed to doses of α particles or γ rays that targeted all cells in the cultures. As expected, α particles were more effective than γ rays at inducing cell killing; further, holding γ-irradiated cells in the confluent state for several hours after irradiation promoted increased survival and decreased chromosomal damage. However, maintaining α-particle-irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 65 publications
(78 reference statements)
5
49
0
Order By: Relevance
“…In this context, our studies have shown that the magnitude of the effects due to connexin channels in enhancing or reducing the propagation of radiation-induced oxidative stress is a function of radiation quality (LET effect). The abundance of reactive species along the track of an HZE particle may be the factor that affects permeability of connexin channels (9)(10)(11). These results are consistent with earlier studies showing that the cellular redox environment together with gap junction communication are the major mediators of the propagation of stressful responses from a particle-irradiated cells to bystander cells in the vicinity (13,17,201,308).…”
Section: Propagation Of Hze Particle-induced Oxidative Damage To Nontsupporting
confidence: 86%
“…In this context, our studies have shown that the magnitude of the effects due to connexin channels in enhancing or reducing the propagation of radiation-induced oxidative stress is a function of radiation quality (LET effect). The abundance of reactive species along the track of an HZE particle may be the factor that affects permeability of connexin channels (9)(10)(11). These results are consistent with earlier studies showing that the cellular redox environment together with gap junction communication are the major mediators of the propagation of stressful responses from a particle-irradiated cells to bystander cells in the vicinity (13,17,201,308).…”
Section: Propagation Of Hze Particle-induced Oxidative Damage To Nontsupporting
confidence: 86%
“…7) Here, we extend these studies and investigate the effect of intercellular communication on the modulation of the stress induced in normal human fibroblasts exposed to particulate radiations found in deep space, namely low LET protons and high-LET iron ions. Characterizing the role of the cross-talk among cells exposed to different types of ionizing radiation may contribute to understanding the effects of radiation quality in the enhancement or mitigation of the induced detrimental effects.…”
Section: Introductionmentioning
confidence: 91%
“…In contrast, a cell traversed by a single electron track resulting from an exposure to X rays receives a small dose of 0.1 cGy [19]. Hence, as in the case of targeted effects, the nature of propagated non-targeted effects is dose-dependent, with low doses to the targeted cells triggering the propagation of an adaptive response and high doses to the targeted cells of agents such as ionizing radiation or chemotherapeutic drugs inducing the spread of toxic effects [20,21]. …”
mentioning
confidence: 99%